2022
DOI: 10.3389/fpsyt.2022.916640
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Predictive Factors of Suicidal Re-attempts in Adolescents and Young Adults After a First Suicide Attempt, a Prospective Cohort Study. Study Protocol of the SURAYA Project

Abstract: IntroductionSuicide is the fourth leading cause of death in youth. Previous suicide attempts are among the strongest predictors of future suicide re-attempt. However, the lack of data and understanding of suicidal re-attempt behaviors in this population makes suicide risk assessment complex and challenging in clinical practice. The primary objective of this study is to determine the rate of suicide re-attempts in youth admitted to the emergency department after a first suicide attempt. The secondary objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 72 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…No correlation was identified between relationship status and drug use across the two periods under study, although such a relationship is evident in the context of psychiatric history and treatment. Current evidence suggests that confinement in isolation and uncertainty can have negative consequences, leading to an increase in mental health problems such as anxiety and depression [9,11,19,20,25]. In contrast, a study conducted in the Czech Republic found that the happiness and quality of life of individuals during the peak of the pandemic was higher than that measured one year before the pandemic.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…No correlation was identified between relationship status and drug use across the two periods under study, although such a relationship is evident in the context of psychiatric history and treatment. Current evidence suggests that confinement in isolation and uncertainty can have negative consequences, leading to an increase in mental health problems such as anxiety and depression [9,11,19,20,25]. In contrast, a study conducted in the Czech Republic found that the happiness and quality of life of individuals during the peak of the pandemic was higher than that measured one year before the pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…Presently, there are concerns about estimating the impact of the COVID-19 pandemic on the mental health of the population [10,11,22]. The COVID-19 pandemic has had a severe impact on the mental health of the population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations